2006
DOI: 10.1002/prot.20867
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐free structure of a monomeric NADP isocitrate dehydrogenase: An open conformation phylogenetic relationship of isocitrate dehydrogenase

Abstract: Both monomeric and dimeric NADP+-dependent isocitrate dehydrogenase (IDH) belong to the metal-dependent beta-decarboxylating dehydrogenase family and catalyze the oxidative decarboxylation from 2R,3S-isocitrate to yield 2-oxoglutarate, CO2, and NADPH. It is important to solve the structures of IDHs from various species to correlate with its function and evolutionary significance. So far, only two crystal structures of substrate/cofactor-bound (isocitrate/NADP) NADP+-dependent monomeric IDH from Azotobacter vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 30 publications
(67 reference statements)
6
41
1
Order By: Relevance
“…2d) similar to the short α-helix loop in CgICD and AvICD (Fig. 2b)2021. Overlaid with EcICD, this short α-helix limits access to the active site and would sterically hinder binding of AceK to the AceK recognition sequence (ARS) (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…2d) similar to the short α-helix loop in CgICD and AvICD (Fig. 2b)2021. Overlaid with EcICD, this short α-helix limits access to the active site and would sterically hinder binding of AceK to the AceK recognition sequence (ARS) (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…2a). A cleft region between the two domains contains the active site, as described for other ICD enzymes2021.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structure-based sequence homology between monomeric and dimeric IDHs is only 7-8%, the tertiary structure of monomeric IDHs (Yasutake et al, 2002;Imabayashi et al, 2006) is similar to that of the well studied dimeric EcIDH (Hurley et al, 1989) and the closely related isopropylmalate dehydrogenase (IPMDH; Imada et al, 1991). Residues binding the substrate isocitrate-Mn 2+ complex are also highly conserved between the two IDHs (Yasutake et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…These include Azotobacter vinelandii (Chung & Franzen, 1969), Colwellia maris (Ochiai et al, 1979;Ishii et al, 1987), R. vannielii (Leyland & Kelly, 1991), Vibrio parahaemolyticus (Fukunaga et al, 1992) and Desulfobacter vibrioformis (Steen et al, 1998). Furthermore, genes or putative genes encoding monomeric IDHs have been described in approximately 50 bacterial species, including pathogenic bacteria such as Mycobacterium tuberculosis, M. leprae, Corynebacterium diphtheriae, Neisseria meningitidis, Vibrio cholerae, Francisella tularensis and Pseudomonas aeruginosa (Yasutake et al, 2002;Imabayashi et al, 2006). The glyoxylate-bypass enzyme isocitrate lyase (ICL) has been shown to help M. tuberculosis persist in mice (McKinney et al, 2000) and ICL and the two IDHs from the bacterium have been suggested as potential drug targets for tuberculosis (TB).…”
Section: Introductionmentioning
confidence: 99%
“…Subfamily I (S1-IDH) consists of homodimeric, prokaryotic and predominantly NADP-dependent IDHs. Subfamily II (S2-IDH)[9,53] consists of homodimeric, predominantly eukaryotic and NADP-dependent IDHs shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%